Prevalence of high‐risk bladder categorization with prenatal and postnatal myelomeningocele repair types. Issue 3 (19th February 2021) - Gerber, Jonathan A.; Stocks, Blair T.; Zhu, Huirong; Castillo, Heidi; Castillo, Jonathan; Borden, Alexandra N.; Tu, Duong D.; Whitehead, William E.; Austin, Paul F.
Abstract: Introduction: Urologic substudies of prenatal myelomeningocele (MMC) closure have focused primarily on continence without significant clinical benefit. Fetoscopic MMC repair (FMR) is a newer form of prenatal intervention and touts added benefits to the mother, but urological outcomes have yet to be analyzed. We set out to focus on bladder safety rather than continence and examined bladder outcomes with different prenatal MMC repairs (FMR and prenatal open [POMR]) and compared bladder‐risk‐categorization to traditional postnatal repair (PSTNR). Methods: An IRB‐approved retrospective analysis of all patients undergoing all forms of MMC repairs with inclusion and exclusion criteria based on the MOMS trial was performed. Bladder safety assessment required initial urodynamic studies (UDS), renal bladder ultrasound (RBUS), and/or voiding cystourethrogram (VCUG) within the 1st year of life. Follow‐up analyses within the cohorts required follow‐up studies within 18 months after initial evaluations. Outcomes assessed included bladder‐risk‐categorization based on the CDC UMPIRE study (high, intermediate, and safe), hydronephrosis (HN), and vesicoureteral reflux (VUR). A single reader evaluated each UDS. Results: Initial UDS in 93 patients showed that the prevalence of high‐risk bladders were 35% FMR versus 36% PSTNR and 60% POMR. Follow‐up UDS showed only 8% of FMR were high‐risk compared to 35% POMR and 36% PSTNR. Change from initial to follow‐up bladder‐risk‐category did not reach significance ( p = .0659); however, 10% PSTNR worsened to high‐risk on follow‐up, compared to none in either prenatal group. Subanalysis of follow‐up UDS between the prenatal cohorts also was not significant ( p = .055). Only 8% of FMR worsened or stayed high‐risk compared to 35% with POMR ( p = .1). HN was significantly different at initial and subsequent follow up between the groups with the least in the FMR group. Conclusions: Early outcome UDS analyses demonstrated lower incidence of high‐risk bladders in FMR patients with a trend toward clinically significant improvement compared to POMR in regard to all evaluated metrics. Larger, prospective, confirmatory studies are needed to further evaluate the potential benefits on FMR on bladder safety and health.